Input Technologies and Techniques (2009) - Hinckley, Ken (Human-Computer Interaction Fundamentals (Human Factors and Ergonomics), 2009)
Input devices sense physical properties of people, places, or things. Yet any treatment of input devices without regard to the corresponding visual feedback is like trying to use a pen without paper. Small-screen devices with integrated sensors underscore the indivisibility of input and output. This chapter treats input technologies at the level of interaction techniques, which provide a way for users to accomplish tasks by combining input with appropriate feedback. An interaction designer must consider the physical sensor, the feedback presented to the user, the ergonomic and industrial design of the device, and the interplay between all of the interaction techniques supported by a system. This chapter enumerates properties of input devices and provides examples of how these properties apply to common pointing devices as well as mobile devices with touch or pen input. We will discuss how to use input signals in applications, and cover models and theories that help to evaluate interaction techniques and reason about design options. We will also discuss discrete symbolic entry, including mobile and keyboard-based text entry. The chapter concludes with some thoughts about future trends.